2002
DOI: 10.1007/s00134-002-1306-6
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of extubation failure predictors in mechanically ventilated infants and children

Abstract: In a population which had passed SBT, the ability of the traditional weaning indices to discriminate between children successfully extubated and children re-intubated is very poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
89
1
29

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(127 citation statements)
references
References 21 publications
6
89
1
29
Order By: Relevance
“…3 Identifying parameters that reliably predict readiness for extubation would improve the quality of care and decrease morbidity and complications related to mechanical ventilation. Studies in adults 10,11 and pediatric patients 12,13 have shown that patients who pass a spontaneous breathing trial (SBT) undergo an extubation readiness trial; 50 -75% are considered ready for extubation. We designed and conducted a survey to determine the frequency of use of extubation readiness parameters such as air leak, rapid shallow breathing index (RSBI), airwayocclusion pressure 0.1 s after the start of inspiratory flow (P 0.1 ), and quantification of secretions and sedation, 3 the methods used, and the attitudes toward these parameters among pediatric critical care physicians.…”
Section: See the Related Editorial On Page 445mentioning
confidence: 99%
“…3 Identifying parameters that reliably predict readiness for extubation would improve the quality of care and decrease morbidity and complications related to mechanical ventilation. Studies in adults 10,11 and pediatric patients 12,13 have shown that patients who pass a spontaneous breathing trial (SBT) undergo an extubation readiness trial; 50 -75% are considered ready for extubation. We designed and conducted a survey to determine the frequency of use of extubation readiness parameters such as air leak, rapid shallow breathing index (RSBI), airwayocclusion pressure 0.1 s after the start of inspiratory flow (P 0.1 ), and quantification of secretions and sedation, 3 the methods used, and the attitudes toward these parameters among pediatric critical care physicians.…”
Section: See the Related Editorial On Page 445mentioning
confidence: 99%
“…6 Bousso et al remark that the difference in results could be reflecting the presence of populations with dissimilar characteristics. This is a common situation when analyzing studies conducted in South America, where there is a predominance of primary respiratory diseases 1,5,[8][9][10]14 compared to the United States or Europe, with predominance of elective surgical patients. 4,6,11,15 At this time, there still are no reliable criteria to predict which patients will require reintubation after tolerating a spontaneous breathing trial.…”
mentioning
confidence: 99%
“…In the study of Farias et al [14], the lehgth of stay on IMV was greater in the group that was unsuccessfully weaned. Fontela et al [15] studied children on IMV and reported that 10.5% required re-intubation within 48 hours after extubation; of these children, those that utilized IMV for more than 15 days suffered the highest extubation failure rate.…”
Section: Discussionmentioning
confidence: 88%
“…The clinical conditions for successful extubation include: adequate respiratory frequency, the absence of the utilization of accessory musculature, the absence of vacillation of the wings of the nose, hemodynamic stability and the absence of convulsive fits [4]. Even so, the selection of the most appropriate time for extubation is one of the most difficult decisions, as there are several publications that identify risk factors of unsuccessful weaning with the criteria varying between the studies; there are no exact protocols in the literature with specific validated data for this group of patients [12][13][14].…”
Section: Introductionmentioning
confidence: 99%